Educational and philosophical dimensions of shattariyyah tariqah : an analytical study of Abd Al-Ra'uf Al Singkili's thought - Zuherni Abubakar (Abdul Hamid Abu Sulayman Kulliyyah of Islamic Revealed Knowledgeand Human Sciences, International Islamic University Malaysia, 2021)
The study aims to gain a proper understanding of shattariyyah tariqah , in which Abd al-Ra’uf is the prime figure to propagate the basics of its teachings, particularly in Aceh. Hence, to explore further details about him, as well as the history behind it. However, focusing Aceh as the main place, in this case, is not simply to figure out shattariyyah teaching in Aceh but to understand its link connection with tariqah and tasawwuf as the agent of disseminating Islam, especially throughout the Malay-archipelago, noted as Negeri diatas angin, the land above the wind. Historically, Islamic tradition had already started in 10th and 11th centuries. However, the 16t\h and 17th centuries are the most important period, that, ‘Abd Ra'uf al-Singkili(d. 1693) together with Hamzah al-Funsuri(d.1590), Shams al-Dinal-Sumatrani (d. 1630), and Nur al-Din al-Raniri (d.1658) become the main figure. It seems that the hand writing tradition of those scholars had contributed to the golden of age Islam in south-east Asia. Regarding the Islamic education, the Acehnese has the specific structure needed to implement. From the earlier period, dayah has taken an important role in Acehnese society, as well as in ts politics. Dayah as a centre of Islamic education conducted a number of disciplines in spreading Islam, leading in rebellions against colonialists, and becoming the centre in tariqah teaching. In this manner, the method used in this study is library research, by tracing a number of ‘Abd al-Ra’Ëf’s writings such as ‘Umdat al-Muhatajin , Tanbih al-Mashi , Sakarat al-Mawt, and Asrar al-Suluk ila al-Muluk and also his tafsir, Tarjuman al-Mustafid. These manuscripts record that ‘Abd al-Ra’uf’s grand master, Shaykh al-Qushashi and Shaykh Ibrahim al-Kurani , were the prominent shaykh, that had influenced him. Shaykh al-Qushashi had taught him the fundamental teachings of shattariyyah tariqah , while Shaykh Ibrahim al-Kurani influenced his philosophical-mystic concept. ‘Abd al-Ra’Ëf seems to have combined both approaches tasawwuf akhlaqi and tasawwuf falsafi. Likewise other Sufi orders, the objective of shattariyyah teaching is to experience closeness with Allah, elaborated from its teachings. ‘Abd al-Ra’uf formulated seven fundamental principles of shattariyyah tariqah . First, the consciousness of the Oneness-Being. Second, the dhikr and its requirement. Third, the prophet Muhammad saw as a dhikr model. Fourth is the meaning of Talqin and Bay’ah. Fifth, the ultimate benefits from the word La ilaha illa Allah. Sixth, the requirement of sunnat prayers, and seventh, the character of the followers of the shattariyyah tariqah .